GM-011 Analysis of benchmarking indicators to achieve quality improvement in a pharmacy department. (14th February 2016) - Sanchez, I; Valiente, F; Rodriguez, MA; Ramos, J; Abellan, L; Fernandez, F; Lucas, C; Villa, E
Abstract : Background: Benchmarking is a process that makes comparing similar companies possible, looking for improvement in best practices. This method can be applied to pharmacy departments but it is necessary to monitor standard quality indicators to develop continuous quality improvement. Purpose: To analyse benchmarking quality indicators (QIs) since they were implemented as a method for continuous quality improvement in a hospital pharmacy department (PhDp). Material and methods: Prospective analysis of 3 years of benchmarking QI data recorded since they were included in the PhDp quality management system (from April 2012 to April 2015). QIs were designed and validated by Benchfar (FBA Consulting), a national project specially designed to compare the performance of pharmacy services. Comparison group was integrated by 28 similar PhDp in terms of number of occupied beds (less than 200 beds). Benchfar online software has been used to record, analyse and compare values for 15 indicators included according to their frequency between member groups: monthly (5), quarterly (1), biannual (3) or annual (6). QIs were divided into three domains: activity (number of pharmaceutical interventions in inpatient prescriptions and cost of expired drugs), technical and scientific quality (stock-out rate, rate of mistakes in distribution unit dose system, rate of short length central parenteral nutritions (less than 5 days), dispensing error rate, number of control temperature deviations, discarded preparation rates) and satisfaction (about the drug information service, dispensing process and nurses and physicians global satisfaction). Results: We were considered similar to the best pharmacy more times for the following QIs: rate of mistakes in distribution unit dose system, stock-out rate and dispensing error rate (in 11, 10 and 8 periods, respectively). According to the percentiles, most of our outcomes were equal to or superior to what is qualified as the minimum level (50th percentile) and we obtained a value superior to the 75th percentile (satisfactory level) in dispensing error rate. However, global satisfaction indicators were below the 50th percentile and monthly pharmaceutical interventions did not always reach the 50th percentile. Conclusion: Benchmarking indicator analysis has made monitoring our performance possible and identified quality improvement opportunities. It is necessary to design and re-evaluate improvement actions to increase the pharmacy client's level of satisfaction and number of interventions. References and/or Acknowledgements: Benchfar. No conflict of interest.